Age-related decline of sleep-dependent consolidation - Spencer, Rebecca M.C.; Gouw, Arvin M.; Ivry, Richard B. (Learning & memory (Cold Spring Harbor, N.Y.), 2007)
Sleep-dependent memory consolidation is observed following motor skill learning: Performance improvements are greater over a 12-h period containing sleep relative to an equivalent interval without sleep. Here we examined whether older adults exhibit sleep-dependent consolidation on a sequence learning task. Participants were trained on one of two sequence learning tasks. Performance was assessed after a 12-h break that included sleep and after a 12-h break that did not include sleep. Older and younger adults showed similar degrees of initial learning. However, performance of the older adults did not improve following sleep, providing evidence that sleep-dependent consolidation is diminished with age.